ANALIZING ACADEMIC PROKRASTINATION CAUSING FACTORS IN DESIGNING THESIS OF ATHLETE STUDENTS - Soegiyanto Soegiyanto; Ipang Setiawan; Moch Fahmi Abdulaziz; Dhimas Bagus Dharmawan; Vivi Septiana Parista (Universitas Negeri Yogyakarta, 2019)
This study was aimed at identifying the factors that caused students of the athletes of the Faculty of Sport Sciences, Semarang State University (UNNES) to carry out procrastination actions in the preparation of the thesis and create a measure of academic procrastination in the preparation of thesis. This study used a mixed method with a sequential exploratory design. The population in this study were the students of Faculty of Sport Sciences, 2010, 2011 and 2012 UNNES who were preparing a thesis. The sampling method used was purposive random sampling. The qualitative data were gathered using questionnaires and interviews, while for quantitative data using the scale of academic procrastination made by the researchers themselves based on the results of qualitative data analysis. Qualitative data analysis technique used was interactive models while Lisrel item analysis was used to analyze quantitative data to confirm which factors had an influence on academic procrastination. The results show that 3 factors causing procrastination namely physical, psychological, and environmental factors. The factors that have the highest influence on academic procrastination are psychic aspects, namely internal factors in each athlete.ANALISIS FAKTOR PENYEBAB PROKRASTINASI AKADEMIK DALAM PENYUSUNAN SKRIPSI PADA MAHASISWA ATLETTujuan dari penelitian ini adalah untuk mengidentifikasi faktor-faktor penyebab mahasiswa atlet Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang (UNNES) melakukan tindakan prokrastinasi dalam penyusunan skripsi serta membuat alat ukur prokrastinasi akademik penyusunan skripsi. Pendekatan dalam penelitian ini adalah dengan menggunakan metode kombinasi (mixed method) dengan rancangan eksploratoris sekuensial. Populasi dalam penelitian ini adalah mahasiswa atlet Fakultas Ilmu Keolahragaan UNNES angkatan 2010, 2011 dan 2012 yang sedang menyusun skripsi, selanjutnya pengambilan sampel dengan menggunakan purposive random sampling. Perolehan Data kualitiatif dikumpulkan dengan instrumen berupa angket dan wawancara, sedangkan untuk data kuantitatif menggunakan Skala prokrastinasi akademik yang dibuat oleh peneliti sendiri berdasarkan hasil analisis data kualitatif. Teknik analisis data kualitatif menggunakan model interaktif sedangkan data kuantitatif menggunakan analisis item Lisrel untuk mengkonfirmasi faktor mana yang memiliki pengaruh terhadap prokrastinasi akademik. Berdasarkan hasil penelitian diperoleh 3 faktor yang menyebabkan prokrastinasi yaitu fisik, psikis, dan lingkungan. Faktor yang memiliki pengaruh paling tinggi terhadap prokrastinasi akademik adalah aspek psikis yaitu faktor internal pada dalam diri mahasiswa atlet masing-masing.